PRECONDITIONS FOR THE DEVELOPMENT OF THE INVESTMENT CONSULTING IN THE UKRAINIAN FINANCIAL SERVICES MARKET - Тяжкороб , Ірина; Євтух , Любов; Лежан , Марія (Socio-economic relations in the digital society, 2019)
Volume and development of the consulting services market considered as an indicator of the market state in the country. Success investment consulting services in Ukraine largely depends on the state support. First of all, the government should ensure a stable economic and political situation, improve of legislation and tax system. Further development of consulting services and the financial market, as a whole, depends on their readiness for innovation, the attraction of foreign  experience and its adaptation to the conditions of socio-economic life of the country; the search of new products and markets; using of new methods of the implementation of the consultation proposals.
Keywords: investment consulting; financial services market; consulting services; development; preconditions